THE INFLUENCE OF ITS OWN STRESSES ON CONCRETE STRENGTH UNDER COMPRESSING - Fenko, О.; Krupchenko, O.; Yurko, I. (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
The results of experimental studies of the impact own stress unevenly distributed over thecross section, for strength of brittle materials were presented. Changes in the distribution ofstresses in own cross-section caused by uneven shrinkage of concrete samples were analyzed.The reasons for own impact stresses are unevenly distributed over the cross-sectional samplefor strength of concrete compressive were justified.Also the effects of stress on its own strength of concrete at its moisture were considered.Described impact on own stress compressive strength is confirmed by experimental resultsobtained by other authors. Shows the distribution of stresses in its own cross section at itswater saturation and drying is not only concrete and also other porous materials.Keywords: own stresses, strength of concrete, water saturated concrete, shrinkage, creep.